1986
DOI: 10.1089/dna.1986.5.383
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Model of the Interaction Between the Glucocorticoid Receptor and the Regulatory Elements of Inducible Genes

Abstract: Binding sites for the glucocorticoid receptor in an ecdysone-inducible gene from Drosophila melanogaster and in the chicken vitellogenin gene are described. A comparison with other binding sites for the glucocorticoid receptor, which have been analyzed by methylation protection experiments, shows they can be classified into three groups. The first group exhibits two blocks of contact points in two subsequent turns of the DNA helix, and includes only functional regulatory elements. The second group shows an ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(31 citation statements)
references
References 24 publications
1
29
0
1
Order By: Relevance
“…CAANNTGTTCT-3', with the 3' hexamer stringently conserved (35). The promoter region of the rat AFP gene Ap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAANNTGTTCT-3', with the 3' hexamer stringently conserved (35). The promoter region of the rat AFP gene Ap.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the enhancer properties of inducible glucocorticoid response elements (7,25), one may further speculate that the AFP glucocorticoid response element might be a glucocorticoid receptor-repressible enhancer. It has also been proposed that glucocorticoid receptors induce and repress genes by using different functional domains (29); perhaps significantly, the left and right segments of the consensus-inducible glucocorticoid response element (35) …”
Section: Discussionmentioning
confidence: 99%
“…The absence of any effect by the other steroids-in particu- induction. To obtain additional support for this surprising observation, the 15-bp oligonucleotide was modified at several sites, some of which are known to be contacted by the glucocorticoid receptor (19,20). The effect of these single or double substitutions upon inducibility by dexamethasone and R 5020 was tested as before.…”
Section: Resultsmentioning
confidence: 99%
“…Close to the center of symmetry of the ERED is the conserved hexanucleotide 5'-TGTTCT-3' on the lower (or antisense strand), which is the core motif for binding to DNA by the glucocorticoid receptor. In vitro receptor-DNA binding studies have shown that this hexanucleotide and neighboring sequences on the VTG II gene are bound by the glucocorticoid receptor (26) and could also possibly be recognized by the androgen receptor (6). The hexanucleotide motif is also part of the recognition sequence of the progesterone receptor (1,14,29).…”
mentioning
confidence: 99%
“…The boxed sequence is the conserved hexanucleotide motif 5'-TGTTCT-3' (in the reversed orientation) shown to bind the glucocorticoid receptor (26). tk = TK.…”
mentioning
confidence: 99%